A Choice Model of Utility Maximization and Regret Minimization. (December 2022) - Hur, Taegyu; Allenby, Greg M.
Consumers often try to achieve multiple goals when purchasing products and services, where choices are sought that maximize utility and other objectives such as to minimize regret. If the performance of choice outcomes are associated with high level of uncertainty at the time of purchase, consumers worry that the alternative of interest may turn out to be not optimal, an outcome they want to avoid when making a purchase. The authors propose a new regret function and explore its properties. Then, they propose a generalized framework of multiple goal pursuit and apply it to a utility maximization and regret minimization problem. Pareto-optimal sets are an outcome of multiple goal optimization problems where there are multiple alternatives that are nondominated. The proposed framework enables the authors to generalize a dual-goal problem as a constrained optimization problem where either utility is maximized subject to the constraint on regret or regret is minimized subject to the utility constraint. The proposed model fits the data better, provides improved predictions, and offers a tractable solution to a problem of utility maximization and regret minimization.